2022
DOI: 10.1016/j.scitotenv.2022.153737
|View full text |Cite
|
Sign up to set email alerts
|

Selection of surrogate viruses for process control in detection of SARS-CoV-2 in wastewater

Abstract: Since SARS-CoV-2 RNA in wastewater is often present at low concentration or under detection limit, ensuring the reliability of detection processes using appropriate process controls is essential. The objective of this study was to evaluate applicability and limitations of candidate surrogate viruses as process controls under combinations of different virus concentration and RNA extraction methods. Detection efficiency of SARS-CoV-2 spiked in wastewater was compared with those of candidate surrogate viruses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Recovery rate using the PMMoV copy number have been conducted for concentration efficiency of wastewater. Previous studies that compared the liquid and solid fraction showed that the detection efficiency of PMMoV ranged 8.0%–30% in the PEG-precipitated liquid fraction and 6.0%–17% in the solid fraction ( Graham et al, 2021 ), and 12%–102% from liquid fractions and 9.4%–62% from solid fractions ( Alamin et al, 2022 ). Our reported recovery values tended to be lower than the range reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery rate using the PMMoV copy number have been conducted for concentration efficiency of wastewater. Previous studies that compared the liquid and solid fraction showed that the detection efficiency of PMMoV ranged 8.0%–30% in the PEG-precipitated liquid fraction and 6.0%–17% in the solid fraction ( Graham et al, 2021 ), and 12%–102% from liquid fractions and 9.4%–62% from solid fractions ( Alamin et al, 2022 ). Our reported recovery values tended to be lower than the range reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 32 SARS-CoV-2 and MHV are, for instance, abundant in the solids fraction of wastewater unlike nonenveloped enteric viruses. 33 For concentration methods including the solid phase, enveloped viruses might be better surrogates. 33 This study started processing with the ultrafiltration method, and therefore MS2 was spiked into the samples as it is known to partition more into the liquid phase.…”
Section: Methodsmentioning
confidence: 99%
“… 33 For concentration methods including the solid phase, enveloped viruses might be better surrogates. 33 This study started processing with the ultrafiltration method, and therefore MS2 was spiked into the samples as it is known to partition more into the liquid phase. For consistency reasons, the use of MS2 for all samples in this study was continued, both for ultrafiltration and centrifugation processed samples.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the recovery rate for PPV in tap water was 5.9% while it was 22.3% for PEDV, which might be explained by the differences in the size and outer layer structure of the virus particles. 55 It is also interesting that the recovery rates in wastewater were not so different from those in tap water ( Figure 2 ). In some cases, the recovery rates of some viruses in wastewater were even higher than those in tap water.…”
Section: Resultsmentioning
confidence: 88%